2006
DOI: 10.1200/jco.2005.04.3190
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Pemetrexed Plus Carboplatin in Malignant Pleural Mesothelioma

Abstract: Treatment with pemetrexed and carboplatin was active and well tolerated in patients with MPM. Disease control rate, time to disease progression, and overall survival were similar to the results achieved with the standard regimen of pemetrexed and cisplatin, suggesting that the carboplatin combination could be an alternative option for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(176 citation statements)
references
References 29 publications
14
160
0
2
Order By: Relevance
“…At present, as cases of malignant mesothelioma of the tunica vaginalis testis are rare, radiation and chemotherapy for malignant testicular mesothelioma remain controversial. Cisplatin and pemetrexed may be used as chemotherapy for testicular mesothelioma (21). In the present case, pemetrexed and cisplatin were administered at a dose of 900 and 130 mg, respectively, on the first day of a 28-day cycle for a total of six chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%
“…At present, as cases of malignant mesothelioma of the tunica vaginalis testis are rare, radiation and chemotherapy for malignant testicular mesothelioma remain controversial. Cisplatin and pemetrexed may be used as chemotherapy for testicular mesothelioma (21). In the present case, pemetrexed and cisplatin were administered at a dose of 900 and 130 mg, respectively, on the first day of a 28-day cycle for a total of six chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing carboplatin to cisplatin, the latter is more commonly associated with neutropenia whereas carboplatin is more likely to cause anemia and thrombocytopenia. Outcomes are otherwise similar suggesting that these therapies may be substituted depending on the particular clinical situation [18].…”
Section: Induction Therapy/chemotherapymentioning
confidence: 99%
“…However, in recent years some evidence suggested that pemetrexed plus cisplatin or carboplatin resulted in superior survival time. [13][14][15] In the present study cohort, a proportion of patients received pemetrexed combined with cisplatin or carboplatin. All patients were followed prospectively at three-monthly intervals for the first year and six-monthly thereafter until the last time of contact or death.…”
Section: Methodsmentioning
confidence: 99%